STRATEGI DAKWAH DALAM PENGUATAN EKONOMI UMAT OLEH GERAKAN PEMUDA (GP) ANSOR KABUPATEN BANYUMAS - Sucipto, Agung Drajat (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2020)
Da'wah is an invitation to change the situation of society from previously unfavorable to better based on the values taught by religion. While the da'wah strategy is the planning steps designed by the preacher in conveying his da'wah material. The choice of da'wah method must be appropriate so that it can be effective. Da'wah bil hal is the most effective method used by researchers in this research. Da'wah bil hal is oriented towards community development through mad'u movements or actions. The preachers in this study were the Gerakan Pemuda (GP) Ansor Banyumas Regency, which is a youth social organization under the auspices of the Nahdlatul Ulama. This study aims to find out what strategies are used by GP Ansor Banyumas to contribute to building the economy of the people. This research is a field, where the data that the authors get by observation and interviews. The collected data were then analyzed using qualitative descriptive analysis method. The result, shows the contribution of GP Ansor Banyumas in strengthening the economy of the people through the tilapia fish cultivation work program, waste bank management, Kietapay. Strong economic development is an alternative to strengthening religious ideology.